The Development of an Instrument to Measure Quality of Vision: The Quality of Vision (QoV) Questionnaire - McAlinden, Colm; Pesudovs, Konrad; Moore, Jonathan E. (Investigative ophthalmology & visual science, 2010)
To develop an instrument to measure subjective quality of vision: the Quality of Vision (QoV) questionnaire. A 30-item instrument was designed with 10 symptoms rated in each of three scales (frequency, severity, and bothersome). The QoV was completed by 900 subjects in groups of spectacle wearers, contact lens wearers, and those having had laser refractive surgery, intraocular refractive surgery, or eye disease and investigated with Rasch analysis and traditional statistics. Validity and reliability were assessed by Rasch fit statistics, principal components analysis (PCA), person separation, differential item functioning (DIF), item targeting, construct validity (correlation with visual acuity, contrast sensitivity, total root mean square [RMS] higher order aberrations [HOA]), and test-retest reliability (two-way random intraclass correlation coefficients [ICC] and 95% repeatability coefficients [R(c)]). Rasch analysis demonstrated good precision, reliability, and internal consistency for all three scales (mean square infit and outfit within 0.81-1.27; PCA >60% variance explained by the principal component; person separation 2.08, 2.10, and 2.01 respectively; and minimal DIF). Construct validity was indicated by strong correlations with visual acuity, contrast sensitivity and RMS HOA. Test-retest reliability was evidenced by a minimum ICC of 0.867 and a minimum 95% R(c) of 1.55 units. The QoV Questionnaire consists of a Rasch-tested, linear-scaled, 30-item instrument on three scales providing a QoV score in terms of symptom frequency, severity, and bothersome. It is suitable for measuring QoV in patients with all types of refractive correction, eye surgery, and eye disease that cause QoV problems.